Kajian Antropolinguistik Ungkapan Pamali Masyarakat Dayak Bakumpai di Desa Pendang Kecamatan Dusun Utara Kabupaten Barito Selatan - Syarah Veniaty; Yulina Mingvianita; Endah Yusma Pratiwi; Jumadi Jumadi (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The Bakumpai community also has written literature that has been published, but according to informants, no results have been obtained from oral literature during the research period. This study examines one of the oral traditions of the Bakumpai community through the expression of taboos in the form of community beliefs as ancestral heritage that is still believed and applied by the community. The expression of taboos is an oral tradition that is still very familiar in the Bakumpai community group who live on the outskirts of the Barito river basin, precisely in Pendang Village, Dusun Utara District, South Barito Regency. This study aims to identify and analyze the existence of pemali as a cultural wealth of the Pendang Village community, Dusun Utara District, South Barito Regency. The research method used is descriptive qualitative research which aims to describe empirically through verbal interaction with stages of data analysis. The study is expected to achieve specific objectives and produce mandatory outputs, namely articles published in the Sinta journal and documents published in books published by HKI, by collecting data on expressions of taboos studied in the field of Anthropolinguistics.